Karakteristik Uji Tarik dan Struktur Makro Plastic Waste dan Serat Bambu - Putra, Wawan Trisnadi; Fadelan; Munaji; Winangun, Kuntang; Dwiprasetya, Chaesar Deserendy (Jurnal Teknik Mesin Indonesia, 2025)
Plastics are widely used in wrapping food, drinks, and household furniture. This research uses materials in the form of shredded HDPE plastic, PET plastic seeds, and ori bamboo fiber. The composition of the mixture used is based on the weight fraction of a 65 gram specimen of mixed material. The main matrix of the mixture was HDPE; PET was added to increase stiffness; and bamboo fiber, as a natural reinforcement that strengthens the bond between components. Which strengthens the bond between the components. Results tensile test results showed the highest average value in specimen composition 1, which is 533.37 N with a tensile stress of 27.77 MPa. In specimen composition 5, the average value of the tensile test was 409.33 N and a tensile stress of 21.31 MPa. Due to the stronger nature of HDPE to bind the bamboo fibers, the tensile strength of the bamboo fibers will increase as the PET content decreases. With decreasing PET content. Macro test results showed that many air bubbles were trapped in the center of the tensile test sample which were not visible from the surface. not visible from the surface. PET plastic is not well mixed in the sample, while the bamboo fibers were well mixed in the test sample.